2012
DOI: 10.5588/ijtld.10.0791
|View full text |Cite
|
Sign up to set email alerts
|

A national infection control evaluation of drug-resistant tuberculosis hospitals in South Africa

Abstract: Background-The importance of infection control (IC) in health care settings with tuberculosis (TB) patients has been highlighted by recent health care-associated outbreaks in South Africa.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
60
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 59 publications
(67 citation statements)
references
References 18 publications
6
60
1
Order By: Relevance
“…Indeed, several studies have shown that in-service training enhances compliance with infection control measures [4346]. Regular training helps to remind the health workers of the importance of these measures.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, several studies have shown that in-service training enhances compliance with infection control measures [4346]. Regular training helps to remind the health workers of the importance of these measures.…”
Section: Discussionmentioning
confidence: 99%
“…The survey questionnaire comprising of four sections – demographic information and knowledge, attitudes and practices (KAP) scales related to TB prevention and infection control-was developed based on instruments used in similar studies [20, 21, 25, 31–35]. The knowledge scale contained 22 statements with the response categories “True”, “False” or “I don’t know”.…”
Section: Methodsmentioning
confidence: 99%
“…A previous study on IC in drug-resistant TB facilities throughout South Africa identifi ed the issue of non-approved respirators (sold as N95) being used. 21 It is critical to ensure a reliable supply of assured quality N95 respirators as part of a comprehensive IC program. Furthermore, integration of OH and IC services would be ideal.…”
Section: Discussionmentioning
confidence: 99%